Pembelajaran Seni Budaya (Musik) Pada Masa Pandemi Covid-19 Di Kelas VIII-1 SMP Negeri 7 Padang - Almatin Taaj Jaya Ali; Irdhan Epria Darma Putra (SENDRATASIK UNP, 2021)
The purpose of this study is to describe the learning of cultural arts, especially music during the Covid-19 pandemic in class VIII-1 of SMP Negeri 7 Padang. This research is classified in the qualitative research with qualitative descriptive methods, the data were collected through literature study, observation, and interviews. The object of this research was a leaning process in art and culture (music) in class VIII-1 of SMP Negeri 7 Padang. The types of data were primary and secondary data. Primary data were obtained directly from sources; a) direct observation of the teaching and learning process with the topic of techniques and styles of singing folk songs; b) interviews with teachers of arts and culture subjects. Based on the data processing, the conclusions are; 1) learning can be done at home, at school, and in the society; 2) from the teacher as the only source of learning turned into various learning resources; 3) from students are told to learn to find out, 4) the method used by the arts and culture teacher is an online method (in a network) which used information and communication technology to increase the efficiency and effectiveness of learning. The results of this research showed that the teaching and learning process had not fully achieved the desired goals.